Sauropus androgynus, Papaya Leaves, and Mung Beans as Mixed Galactagogue Drink for Urban Postpartum Mothers - Ngadiarti, Iskari; Agestika, Lina; Srimiati, Mia; Fayasari, Adhila (Jurnal Gizi dan Pangan, 2021)
This study explored the effect of Sauropus androgynus, papaya leaves, and mung beans as mixed galactagogue drinks on breastmilk volume, frequency, and duration among urban postpartum mothers in Jakarta. A quasi-experimental study with 60 postpartum mothers divided in intervention and control groups was conducted. The intervention group was administered with a 400-cc traditional galactagogue drink daily within 4 weeks of postpartum, while the control group received 3 times breastfeeding counselling. The breastmilk volume was measured using the evaporative water loss method on mothers’ weight at the first, second, third-, and fourth-week consumption. The mean difference of breastmilk volume, breastfeeding frequency, and duration between the intervention and control groups was calculated by bivariate analysis using an independent sample t-test. The breastmilk volume was not different between both groups on the first and second week (1st:622.93±289.24 and 507.68±231.28, p=0.094; 2nd:683.00±252.42 and 582.58±225.42, p=0.110), however, the intervention group had higher volume than the control group in the third and fourth week (3rd:801.43±273.35 and 656.24±214.43, p=0.026; 4th=908.52±271.27 and 756.69±196.29, p=0.016). No significant difference was observed in the breastfeeding frequency and duration among the groups. In conclusion, the new galactagogue mixed drink consumption has the potential to increase breastmilk production and enhance a mother’s confidence to continue breastfeeding.